The greater game : India's race with destiny and China - Van Praagh, David (McGill-Queen's University Press, 2003)
The Greater Game offers a fresh look at India, showing it to be a dramatically changing democracy after decades of domination by the Nehru-Gandhi family dynasty and a newly emerging strategic ally of the United States. David Van Praagh argues that Hindu nationalists, the country's new paramount political force, are creating a new kind of coalition politics that discourages religious clashes. Led by the Bharatiya Janata Party they are also bringing about needed economic liberalization. Since coming to power in 1998, the Hindu nationalists led by Atal Bihari Vajpayee and Lal Krishna Advani have brought India out of the nuclear closet with a series of tests confirming its status as a nuclear power. After the terrorist attacks on 11 September 2001 on America and three months later on the Indian Parliament, the United States and India have quietly become "allies in the cause of democracy," with an eye to containing not only terrorists but China. Van Praagh, a journalist with many years of experience in India and Asia as a correspondent for western newspapers, combines first-hand coverage of events, historical narrative, and timely analysis in this clearly written and provocative book. The Greater Game details India's political evolution and that country's emergence as not only the pre-eminent power in the Subcontinent but also a major world power